2011
DOI: 10.1002/adem.200900287
|View full text |Cite
|
Sign up to set email alerts
|

Stress Corrosion Cracking of Magnesium Alloys

Abstract: An overview is provided of our current understanding of SCC of Mg alloys. TGSCC is caused by an interaction of H with the microstructure so a detailed study of H-trap interactions is needed in order to design alloys resistant to TGSCC. This understanding is urgently needed because prior research indicates that many Mg alloys have a threshold stress for stress corrosion cracking of the order of half the yield stress in common environments including high-purity water.SCC fracture surface for AZ91 showing fractur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
25
0
3

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
2
1

Relationship

4
4

Authors

Journals

citations
Cited by 59 publications
(29 citation statements)
references
References 61 publications
(109 reference statements)
1
25
0
3
Order By: Relevance
“…Mg alloys also suffer stress corrosion cracking (SCC) [16,17]. SCC can occur at stresses as low as 50% of the yield stress.…”
Section: Introductionmentioning
confidence: 99%
“…Mg alloys also suffer stress corrosion cracking (SCC) [16,17]. SCC can occur at stresses as low as 50% of the yield stress.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that the SCC of Mg alloys occurs through transgranular stress corrosion cracking (TGSCC), intergranular stress corrosion cracking (IGSCC), or a mixed TGSCC/IGSCC mode 43,44) . The mode of SCC depends on the composition 44) and microstructure 45) of the alloy and possibly on environmental factors such as pH 25) .…”
Section: Effect Of Sn Content On Crack Propagationmentioning
confidence: 99%
“…The mode of SCC depends on the composition 44) and microstructure 45) of the alloy and possibly on environmental factors such as pH 25) . Figure 10 shows cross-section images of HA and SHT samples after bentbeam stress corrosion tests conducted for 1 d. As evident in the gure, the mechanism for SCC of the HA and SHT samples was IGSCC.…”
Section: Effect Of Sn Content On Crack Propagationmentioning
confidence: 99%
“…Stress corrosion cracking (SCC) is known to be an issue for Mg alloys [1][2][3] and this topic has recently received considerable attention [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23]. The reviews by Winzer and co-workers [1][2][3] on the stress corrosion cracking (SCC) of Mg alloys showed that SCC can occur at stresses equal to 50% of the yield stress.…”
Section: Introductionmentioning
confidence: 99%
“…The reviews by Winzer and co-workers [1][2][3] on the stress corrosion cracking (SCC) of Mg alloys showed that SCC can occur at stresses equal to 50% of the yield stress. A continuous second phase along grain boundaries causes intergranular stress corrosion cracking (IGSCC).…”
Section: Introductionmentioning
confidence: 99%